Coleopteran Diversity at the three selected areas in Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2022)
The diversity of coleopteran species was studied at three different selected areas in Dhaka city from December 2016 to November 2017. A total of 11,397 individuals of 56 coleopteran species belonging to 50 genera, including 15 families, were recorded in the study areas during the study period. Of them, 47 species (4916 individuals) of 13 families were found at the Ramna Park, 48 species (2441 individuals) of 15 families at the National Botanical Garden, and 42 species (4040 individuals) of 11 families at the Atomic Energy Research Establishment (AERE) campus. A total of 30 species, 25 genera, and 11 families were common in these three study areas. At the Ramna Park, the highest species richness included the family Chrysomelidae (34.04%), and the lowest was under the six families including Staphylinidae, Bostrichidae, Nitidulidae, Geotrupidae, Erotylidae, and Scarabaeidae (2.13%). At the National Botanical Garden, the maximum number of species was recorded under the family Chrysomelidae (6.24%), and the lowest was under seven families including Staphylinidae, Bostrichidae, Nitidulidae, Geotrupidae, Erotylidae, Elateridae, and Dermestidae (2.08%). The maximum number of coleopteran species was identified under the family Chrysomelidae (35.71%), and the lowest was under six families including Staphylinidae, Cerambycidae, Nitidulidae, Geotrupidae, Elateridae, and Dermestidae (2.38%) at the AERE campus. The Shanon’s Diversity Index (H′) and Simpson’s Index (λ) indicate high coleopteran diversity at the Ramna Park (H′=3.41, λ=0.05), the AERE Campus (H′=3.07, λ=0.06), and the National Botanical Garden (H′=2.93, λ=0.08). The high species evenness in the Ramna Park (J’= 0.89) and the AERE campus (J’= 0.82) indicates that the species were evenly distributed, whereas at the National Botanical Garden (J’= 0.76) they were comparatively less evenly distributed. The calculated Sorenson’s Coefficient (CC) is 0.66, indicating that these three communities were fairly similar or overlapped. The Community Dominances were 21.03%, 32.16% and 18.66% for the Ramna Park, National Botanical Garden, and AERE campus, respectively.Bangladesh J. Zool. 50 (2): 185-200, 2022